The effectiveness of Promoting Alternative Thinking Strategies program: A meta-analysis - Shi, Jieping; Cheung, Alan C. K.; Ni, Aohua (Frontiers in Psychology, 2022)
Promoting Alternative Thinking Strategies (PATHS) is a widely-used social emotional learning program for preschool and elementary school students. The purpose of this review is to examine its effects, and explore the moderation effects of methodological and implementation features on intervention effectiveness. Using stringent inclusion criteria, 20 qualified studies and 177 effect sizes involving 30,454 participants were included. Results showed that the overall effect size of PATHS was 0.11. In particular, the effect size of PATHS on social emotional skills (ES=0.16) was the largest compared with other outcome domains, including attitude or relations (ES=0.08), emotional well-being (ES=0.02), prosocial behaviors (ES=0.04), conduct problems (ES=0.06) and academic performance (ES=0.05). There was no differential impact of PATHS on regular students and targeted students. Research design, sample size, and intervention dosage could moderate the effectiveness of PATHS significantly, and dosage was the predominant factor in determining the effects of PATHS. Policy and practical implications were discussed.